HC-Pro inhibits HEN1 methyltransferase activity, leading to autophagic degradation of AGO1 - Zhao-Jun Pan; Wei-Lun Wei; Phuong-Anh Tran; Ru-Ying Fang; Thanh Ha Pham; John L. Bowman; Chao-Tzu Chung; Bing-Nan Shen; Ju-Ting Yang; Han-Han Chang; Wann-Neng Jane; Chiung-Hsiang Cheng; et al. (Nature Communications)
Abstract Helper-component proteinase (HC-Pro), encoded by potyviruses, function as viral suppressors of RNA silencing (VSRs). Despite their conserved role, HC-Pros share approximately 40% similarity, implying potential differences in VSR efficiency, particularly in their ability to inhibit HEN1 methyltransferase activity. This study investigated the inhibitory potential of HC-Pros from different potyviruses in transgenic plants. P1/HC-Pro from turnip mosaic virus (P1/HC-ProTu) exhibited the most potent inhibition of HEN1, followed by P1/HC-Pro from zucchini yellow mosaic virus (P1/HC-ProZy), while P1/HC-Pro from tobacco etch virus (P1/HC-ProTe) showed the weakest inhibitory effect. These differential effectual effects corresponded to variations in unmethylated microRNAs (unMet-miRNAs) accumulation across the transgenic lines. Fluorescence resonance energy transfer (FRET) analysis indicated that HC-ProTu recruits HEN1 and ATG8a to HC-Pro bodies (H-bodies) and indirectly associates with AGO1, potentially influencing the assembly of the RNA-induced silencing complex (RISC) and leading to the accumulation of free-form miRNA duplexes. The ability of HC-ProTu to sequester HEN1 and AGO1 in H-bodies may, therefore, modulate miRNA loading. This observation aligns with the finding that P1/HC-Pro Tu plants harbored approximately 50% unMet-miRNAs and exhibited the lowest AGO1 levels, suggesting a positive correlation between HEN1 inhibition and autophagic degradation of AGO1. Interestingly, unMet-miRNAs are absent in the AGO1 of P1/HC-Pro Tu plants but reappeared in P1/HC-Pro Tu /hen1-8/heso1-1 plants, accompanied by signs of AGO1 recovery. These findings highlight the functional diversity of HC-Pro VSRs and provide new insights into their differential effects on miRNA methylation, RISC assembly, and the regulation of RNA silencing pathways.